Computer- and Telephone-Delivered Interventions on Patient Outcomes and Resource Utilization in Patients With Orthopaedic Conditions: A Systematic Review and Narrative Synthesis. (September 2020) - Jansson, Miia Marika; Hyvämäki, Piia; Pikkarainen, Minna
Abstract : BACKGROUND: As the number of patients with orthopaedic conditions has risen continuously, hospital-based healthcare resources have become limited. Delivery of additional services is needed to adapt to this trend. PURPOSE: The purpose of this study was to describe the current literature of computer- and telephone-delivered interventions on patient outcomes and resource utilization in patients with orthopaedic conditions. METHODS: The systematic review was conducted in January 2019. The standardized checklist for randomized controlled trials was used to assess the quality of the relevant studies. A meta-analysis was not possible due to heterogeneity in the included studies, and a narrative synthesis was conducted to draw informative conclusions relevant to current research, policy, and practice. RESULTS: A total of 1, 173 articles were retrieved. Six randomized controlled trials met the inclusion criteria, providing evidence from 434 individuals across four countries. Two studies reported findings of computer-delivered interventions and four reported findings of telephone-delivered interventions. The patients who received both computer- and telephone-delivered interventions showed improvements in patient outcomes that were similar or better to those of patients receiving conventional care. This was without any increase in adverse events or costs. CONCLUSION: Computer- and telephone-delivered interventions are promising and safe alternatives to conventional care. This review, however, identifies a gap in evidence of high-quality studies exploring the effects of computer- and telephone-delivered interventions on patient outcomes and resource utilization. In future, these interventions should be evaluated from the perspective of intervention content, self-management, and patient empowerment. In addition, they should consider the whole care journey and the development of the newest technological innovations. Additionally, future surgery studies should take into account the personalized needs of special, high-risk patient groups and focus on patient-centric care to reduce postdischarge health problems and resource utilization in this population.